The GAMMA-400 gamma-ray telescope for precision gamma-ray emission investigations. Issue 3 (January 2016) - Topchiev, N P; Galper, A M; Bonvicini, V; Adriani, O; Aptekar, R L; Arkhangelskaja, I V; Arkhangelskiy, A I; Bakaldin, A V; Bergstrom, L; Berti, E; Bigongiari, G; Bobkov, S G; et al.
Abstract: The GAMMA-400 gamma-ray telescope with excellent angular and energy resolutions is designed to search for signatures of dark matter in the fluxes of gamma-ray emission and electrons + positrons. Precision investigations of gamma-ray emission from Galactic Center, Crab, Vela, Cygnus, Geminga, and other regions will be performed, as well as diffuse gamma-ray emission, along with measurements of high-energy electron + positron and nuclei fluxes. Furthermore, it will study gamma-ray bursts and gamma-ray emission from the Sun during periods of solar activity. The GAMMA-400 energy range is expected to be from ∼20 MeV up to TeV energies for gamma rays, up to 10 TeV for electrons + positrons, and up to 10 15 eV for cosmic-ray nuclei. For 100-GeV gamma rays, the GAMMA-400 angular resolution is ∼0.01° and energy resolution is ∼1%; the proton rejection factor is ∼5x10 5 . GAMMA-400 will be installed onboard the Russian space observatory.